Leveraging Local Agricultural Commodities for Early Stunting Prevention: A Quasi-Experimental Trial of a Corn and Mung Bean Supplementary Flour in Rural Toddlers - Ayu Dewi Nastiti Nastiti; R.A. Helda Puspitasari; Dwining Handayani; Esa Rosyida Umam; Nurul Fahmi Rizka Laily (Health and Technology Journal (HTechJ), 2026)
Stunting in rural agricultural areas is exacerbated by inadequate nutrient intake and limited access to commercial supplements. This study evaluated the effectiveness of a locally formulated modified Modisco flour, comprising corn and mung beans, on body weight gain among toddlers at risk of stunting. A quasi-experimental pretest–posttest control-group design was employed, involving 36 at-risk toddlers in Pasuruan Regency, Indonesia, who were purposively allocated to intervention (n=18) and control (n=18) groups. The intervention group received daily modified Modisco flour supplementation for four weeks alongside standard nutritional care, whereas the control group received standard care only. Anthropometric data were analyzed using paired and independent t-tests. Following the four-week intervention, the intervention group exhibited a significant mean weight increase of 1.10 kg (from 9.10 ± 0.85 kg to 10.20 ± 0.92 kg; p = 0.001). The control group showed a marginal increase of 0.30 kg (from 9.20 ± 0.88 kg to 9.50 ± 0.90 kg; p = 0.041). The mean weight gain was significantly greater in the intervention group compared to the control group (p = 0.003). Supplementation with corn- and mung bean-based modified Modisco flour significantly enhances short-term weight gain in toddlers at risk of stunting. These findings underscore the viability of leveraging locally available agricultural commodities as a sustainable, community-based strategy for early stunting prevention in resource-constrained settings.